EFEKTIFITAS PEMBERIAN BISKUIT IKAN BILIH (Mystacoleucus padangensis) TERHADAP STATUS GIZI DAN MORBIDITAS - Marni Handayani; M. Husni Thamrin (Politeknik Kesehatan Kementerian Kesehatan Banten, 2015)
The problem of malnutrition in children under five years is not a new thing, but the problem is still actual . One of the alleviation program for malnurition problem is food supplementation. The biscuits are used as food supplementation in the community , is still a food manufacturer based flour and it hasn’t enriched yet by exploring the potential of local food that is rich in nutrients, such as fishery products. This research was aimed to see the effect of Bilih fish (Mystacoleucus padangensis) biscuits on nutritional status and morbidity of malnutrition children under five years in the region of Belimbing Health Centre, Padang city. The study is an experimental research with pre-post test one group design. Preliminary research was done to get the formula Bilih fish flour biscuits by using a completely randomized design (CRD) continued by acceptance with organoleptic test. The subjects of the research were children ages 2-5 years who where WAZ-scores ≤ -2 SD conducted purposively. The treatmen was given 5 times a week for 3 week. Data collected by antrophometry for nutritional status, interview for morbidity and 24 hour- recall for intake energy and nutritions. Data was analyzed in the continuous stages: data analysis to obtain the best functional biscuit formulation was obtained by ANOVA test with 95 % confidence level. The effect of Bilih fish biscuits on nutritional status and morbidity was analyzed by paired T-Test. It was found that the best biscuits formula from Bilih fish was formula F1 (Addition 10 gr of Bilih Fish flour, 500 kkal energy, 7,8 gr protein and 1,9 mg zinc). The average change of WAZ-scores was 0,2 SD after treatmen. There was a decline in the number of children under five suffering from diarrhea and acute respiratory infection after treatment. There was a difference of nutritional status, intake of energy and nutrients, suffering from acute respiratory infection before and after giving the biscuits from Bilih fish flour. There was no difference in suffering from diarrhea before and after treatmen. Giving the biscuits from bilih fish flour can increase WAZ-score. Further research conducted need to look at the acceptability and the efficacy of Bilih fish flour usage in the food processing techniques to improve the value of the food nutrition.